Assessment of COVID-19 Vaccine Acceptance and Reluctance Among Staff Working in Public Healthcare Settings of Saudi Arabia: A Multicenter Study - Maqsood, Muhammad Bilal; Islam, Md. Ashraful; Al Qarni, Ali; Nisa, Zeb-un-; Ishaqui, Azfar Athar; Alharbi, Naif Khalaf; Almukhamel, Murtaja; Hossain, Mohammad Akbar; Fatani, Nayyra; Mahrous, Ahmad Jamal; Arab, Muhammad Al; Alfehaid, Fahad Sami Abdulaziz; et al. (Frontiers in Public Health, 2022)
Objective The study aimed to evaluate the COVID-19 vaccination acceptance and reluctance among staff working in Saudi healthcare facilities. Methods A cross-sectional study was conducted during April – May 2021, among healthcare workers in five public hospitals under the National Guards Health Association located in Alahsa, Dammam, Jeddah, Madinah, and Riyadh. The study used a questionnaire in English language that was distributed through official email communication among healthcare staff currently working at study venues. The data was analyzed using IBM SPSS v23. An ethical approval was obtained. Results A total of 1031 responses were recorded. Most of the staff had both doses of COVID-19 vaccine (89%). The mean score for vaccine acceptance on a scale of 1 (strongly disagree) to 5 (strongly agree) was 3.55 ± 1.6. The mean score for vaccine reluctance on the same scale was 2.71 ± 1.05. Most participants mentioned safety (76.9%), and efficacy (56.3%) as vaccine concerns and believed that COVID-19 vaccine may not be effective because of changes in virus strain (55.5%). The variables of gender and nationality significantly affected vaccine acceptance while age, gender, nationality, and profession significantly affected vaccine reluctance (p<0.05). Conclusion Most healthcare staff were vaccinated and a high acceptance for COVID-19 vaccination was reported. Several demographic factors affected the vaccine acceptance and reluctance.